2021
DOI: 10.1093/braincomms/fcab170
|View full text |Cite
|
Sign up to set email alerts
|

Garcinia kola improves cognitive and motor function of a rat model of acute radiation syndrome in the elevated plus maze

Abstract: We reported recently that the elevated plus maze is a good tool for evaluating cognitive and motor functional changes in gamma-irradiated rats as a model for new drug evaluation and monitoring. The capacity of Garcinia kola to mitigate radiation-induced brain injury is currently unknown. We therefore assessed the effects of the neuroprotective medicinal plant Garcinia kola, on the cognitive and motor changes in this murine model of acute radiation syndrome. Wistar rats exposed onc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Subfractions F2–F5 of ethyl acetate also improved the animal condition, nervous system dysfunction signs, and performance on the HGT of diabetic animals. Subfraction F5, which had the strongest effects, improved all factors measured in diabetic animals and restored the body weight to values comparable to the nondiabetic vehicle group, as in studies performed with crude G. kola and extracts [ 24 , 25 ] and in models of neurodegenerative diseases and conditions [ 26 , 44 47 ], indicating that F5 contains at least some major neuroprotective constituents of G. kola . Furthermore, F5 effects were dose dependent.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Subfractions F2–F5 of ethyl acetate also improved the animal condition, nervous system dysfunction signs, and performance on the HGT of diabetic animals. Subfraction F5, which had the strongest effects, improved all factors measured in diabetic animals and restored the body weight to values comparable to the nondiabetic vehicle group, as in studies performed with crude G. kola and extracts [ 24 , 25 ] and in models of neurodegenerative diseases and conditions [ 26 , 44 47 ], indicating that F5 contains at least some major neuroprotective constituents of G. kola . Furthermore, F5 effects were dose dependent.…”
Section: Discussionmentioning
confidence: 60%
“…These effects were mediated partly by protecting cerebellar neurons from apoptosis and by decreasing neuroinflammation [ 24 , 25 ]. Moreover, we recently reported the ability of G. kola to improve cognitive and motor functions in a rat model of acute radiation syndrome [ 26 27 ]. Interestingly, at the same time, other recent studies also reported G. kola neuroprotective activities in various models of neurodegenerative diseases and conditions [ 28 31 ], calling for further studies to develop neuroprotective drugs from G. kola seeds.…”
Section: Introductionmentioning
confidence: 99%
“…112 Wistar rats were exposed to gamma radiation followed by treatment with an ethyl acetate fraction of a methanolic extract of Garcinia kola seeds. 112 The treatment at a concentration of 100 mg kg −1 of the extract was carried out for 9 weeks. The elevated plus-maze experiments were performed to evaluate the cognitive and motor functions in irradiated groups and non-irradiated control rats.…”
Section: Fruits As Radioprotective Agentsmentioning
confidence: 99%
“…In summary, the analysis revealed that the Garcinia kola seeds have protective properties against the decline in cognitive and motor development in the acute radiation syndrome. 112…”
Section: Fruits As Radioprotective Agentsmentioning
confidence: 99%
See 1 more Smart Citation